REVITALISASI PEMBELAJARAN AL-QUR’AN DAN BAHASA ARAB BAGI PEMULA: SINERGI DAKWAH, PENDIDIKAN, DAN PENGABDIAN - Ahmadi; Ismail; Septyana Tentiasih; Eka Danik Prahastiwi (DEVELOPMENT: Journal of Community Engagement, 2025)
The declining ability to read the Qur’an and the limited understanding of basic Arabic among Muslim communities indicate the need for a more participatory and educational approach to da‘wah. This community service program was initiated by the Lembaga Pengembangan Cabang dan Ranting (LPCR) of the Pimpinan Daerah Muhammadiyah (PDM) Pacitan as an effort to foster synergy between Islamic outreach (da‘wah), education, and community empowerment. The program aimed to revitalize Qur’anic reading and basic Arabic learning for beginners through training in Qur’anic recitation (tajwīd), introduction to basic Arabic vocabulary and structures, and continuous mentoring using simple digital media. The implementation involved several stages, including need assessment, classical and peer tutoring sessions, and mosque-based monitoring. The results revealed significant improvement in participants’ ability to read the Qur’an correctly, their mastery of elementary Arabic vocabulary, and their motivation to sustain learning as part of daily worship. This initiative demonstrates an effective model of collaboration between LPCR Muhammadiyah and local communities in developing contextual Islamic literacy that is sustainable, inclusive, and transformative.